Fresno County Bar Association Legislators' Reception at The Downtown Club - Watkins, Howard::::::::: (1988)
State Senator Rose Ann Vuich, Gary Waldron, Chris Moore, Bob Fishman (in background), ?, and Robert Bergstrom